Integrating Solar Cell Technology, Radio Waves, and AI for a Transformative IT Business Ecosystem: A Comprehensive Review - Mohammad Ali (Information Technology and Science (ITScience), 2024)
The convergence of radio waves, solar cell technology, and artificial intelligence (AI) has ushered in a new era of innovation with significant consequences for the business and information technology (IT) sectors in a world characterized by rapid technological advancement. This thorough review examines the three domains' synergistic integration, analyzing its transformative potential and possible uses. The voyage begins with an examination of solar cell technology, clarifying its various varieties and uses. The importance of radio waves in the IT industry is then discussed, covering everything from conventional radio broadcasting to state-of-the-art wireless communication networks. With an emphasis on data analytics, process automation, and decision support systems, the function of AI in corporate operations is examined. The review's study of radio wave devices powered by solar cells forms its core. We explore their potential to power solar-powered energy harvesting and AI-driven optimizations to build durable, clean, and trustworthy communication infrastructures. Case studies highlight the observable achievements in domains including precision agriculture, environmental monitoring, disaster response, and telecommunications. But this integration is not without its difficulties and considerations. These include regulatory issues, technical difficulties, and the intricate relationship between social and environmental duties. A comprehensive understanding of the terrain is provided by the careful analysis of these factors. The final section of the paper looks at new developments in the field, highlighting the important roles played by startups, cooperative industrial projects, and an emphasis on environmentally sustainable practices. It also discusses the prospects and potential for the future, including the changing market, developments in AI and solar cell technologies, as well as the rise of new industries and services.